Arquétipos rodonianos: o lugar da América Latina na história ocidental - Maciel, Renata Baldin (2014)
This dissertation was developed on line of research of Integration, Politic and Border on History Master degree of Post graduation Program of Universidade Federal de Santa Maria with with funding from FAPERGS/CAPES. In considering the uruguayan José Enrique Rodó intellectual (1871- 1917) that composed an historical narrative that offered a place for Latin America in Western history, the goal of this dissertation is to discuss what were the strategies and cloth discursive fund established by Rodó in building Americanist ideal as an instrument for the defense of Latin American identity and continental unity. Thus, we sought to perform an analysis that included the corpus of the writer, in order to verify the continuities and ruptures in historical thought. The sources used are constituted by works Ariel (1900), Motivos de Proteo (1909), Liberalismo y Jacobinismo. La expulsion de los crucifijos (1906), El Mirador de Próspero (1913) and some of his political and literary essays published in newspapers and magazines Rodó. In the first chapter, the discussion turned to the contextual levels that involve the relationship of culture and society with the text. With these contextual levels aimed to interpret the writings of Rodó from his political and literary activities. In this chapter were prioritized the political, social and cultural events of the late nineteenth and early twentieth century with which Rodó has been involved, especially those pegged the figure of José Batlle y Ordóñez, Modernism and the Generation of 900. In the second chapter, the interpretive axis turned to problematize the proximity of rodoniana work with the characters of The Tempest (1611-13) of W. Shakespeare, as for models of the philosophy of history of the eighteenth-century German idealism, specifically Kant and Hegel and Comte's positivism of the nineteenth century. In the third chapter were problematized models of civilization constituted by the triad Latin America-United States-Europe, understood from a relational perspective. In this chapter also the concepts of democracy and Latin America were analyzed. In light of the discussion was possible to verify the existence of continuity of thought in rodoniano racing employment of W. Shakespeare characters as archetypes in human terms used to think Western civilization. Moreover, the rejection of the utilitarian spirit, criticism democracy of his time, the appeal to youth, the idea of progress, defending the tradition of the race and rush to the values of Classical Greece and Christianity can be considered as the expression maximum of the philosophy of history in that Rodó demonstrate its commitment to consolidate a place in the world to Latin America. In a progressive perspective, youth would be responsible for evolution and enhancement of the values of society while the triad Latin America- United States-Europe represent the core of identify formation called Euro-Latin-America .